EVALUATION OF RISK FACTORS ON HEARING ABILITY IN INFANTS AT RISK BY BERA - DR.BHAGYA V; DR.BHAGYA V (International Journal of Pharma and Bio Sciences, 2014)
Incidence of severe hearing loss among survivors of neonatal intensive care who are exposed to multiple risk factors ranges from 1% to 28%. So the present study is done to know the incidence of hearing loss in infants at risk and to evaluate the effect of risk factors on hearing. 128 risk infants exposed to multiple risk factors viz; prematurity, birth asphyxia, LBW , hyperbilirubinemia and neonatal seizures were evaluated using RMS EMG. EP MARK –II machine . On multiple logistic regression analysis however only hyperbilirubinemia was found to be significantly correlated (p-value <0.05) with hearing impairment in the affected infants and infants without neonatal seizures showed protection from deafness signifying that it is a risk factor for deafness. Screening of high risk infants by BERA at the earliest will help in their rehabilitation and normal developmental milestones.